Leadership Complexities of School Heads in Multigrade Education - Bojos, Windel; Almerez, Queenie Lyn; Trinidad, Amelie; Arnado, Jeric Anthony; Fuentes, Augie (Journal of Interdisciplinary Perspectives, 2025)
This study explored the experiences of multigrade school heads, focusing on the challenges they face in balancing teaching and administrative duties amid staffing shortages and limited resources. Using a phenomenological qualitative approach, eight multigrade school leaders who served as school leaders and classroom teachers were interviewed. The data were manually transcribed, coded, and analyzed using thematic analysis, with confidentiality maintained throughout the process. The results highlighted the challenges faced, strategies employed, and the support multigrade school heads need in carrying out their complex roles. The challenges were summarized under the central theme: Thriving Through Innovation, Resilience, and Effective Management. The strategies were captured in the theme: Enhancing Multigrade Education Through Adaptability and Support. Lastly, the support needs were reflected in the theme: Strengthening Multigrade Education Through Policy, Support, and Collaboration. The study results revealed that multigrade school heads face significant challenges, which were encapsulated in the theme "Thriving Through Innovation, Resilience, and Effective Management," highlighting their need to constantly adapt and lead despite limited resources and staffing shortages. In response to these challenges, they employed various strategies, captured in the theme "Enhancing Multigrade Education Through Adaptability and Support," demonstrating their flexibility and reliance on internal and external support systems. Furthermore, their expressed needs for sustained assistance were reflected in the theme "Strengthening Multigrade Education Through Policy, Support, and Collaboration," emphasizing the importance of clear policies, adequate resources, and strong partnerships to ensure multigrade education’s long-term effectiveness and sustainability.